2019
DOI: 10.18203/2394-6040.ijcmph20194471
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of knowledge and practice of handling chemotherapy agents by nurses: a multi-centre studies in Bangladesh

Abstract: Background: Along with several significant factors in chemotherapy treatment management’s nurses plays the pivotal role. The objective of this study was to evaluate the knowledge of nurses in relation to handling chemotherapy and the current practice of cancer centers in different hospitals in Bangladesh.Methods: The cross-sectional study was designed based on anonymous self-administered questionnaire. The questionnaire was developed from literature and expert input and validated by subject experts.Results: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…Moreover, it has been observed that nurses who have in-depth knowledge on drug handling were very confident than those with average understanding [13]. Hosen MS, et al also reported similar findings [14].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Moreover, it has been observed that nurses who have in-depth knowledge on drug handling were very confident than those with average understanding [13]. Hosen MS, et al also reported similar findings [14].…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, study conducted by Angel RG, et al showed mean knowledge score of Pre-test 6.78 (± 1.24) and post-test 19.11 (± 1.23) and the 't' value of 44.63 which is significant at 0.001 level of significance [15]. Another study conducted by Hosen MS, et al also reported that nurses do not have adequate knowledge about use of personal safety equipment's and regarding safe handling of chemotherapeutic drugs [14]. Furthermore, the current study discerns that the level of knowledge regarding safe handling of chemotherapeutic drugs among nurses was significantly associated…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Education and training can raise awareness of hospital personnel on the potential hazards of working with cytostatic agents. Previous research in low-and middle-income countries showed that this could be a reason for non-compliancy with safety guidelines (18)(19)(20)(21)(22)(23). Some extremely high levels of cytostatics were probably caused by spilling and remained on the surfaces by inadequate cleaning or cleaning protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Since engineering controls such as biosafety cabinets are costly, healthcare workers in low-and middle-income countries have to rely more on other measures to control hazard (e.g., personal protective equipment) (17). However, studies on safe handling of cytostatic drugs among healthcare workers in middle-income countries reported insufficient or complete lack of specialized training, inappropriate cleaning procedures and a high variability in awareness of potential hazards and use of personal protective equipment (18)(19)(20)(21)(22)(23). In general, these studies indicate the need for a better implementation of guidelines.…”
Section: Introductionmentioning
confidence: 99%